Virtual language creativity in the service of humour on the internet (Philology, 2024)
The article addresses humorous texts in informal internet discourse as a result of the linguo-creative thinking of the network person. It examines samples of language play in such digital hybrid genres as memes and their varieties. Furthermore, the article describes the author’s techniques actively used within the framework of virtual word-making and analyses some of the linguistic and supra-lingual features which have a serious impact on the quality of comic utterance; the latter is examined from the point of view of various theories of humor as well.
Keywords: internet; language pun; linguo-creativity; word-making; humor